The flat tax - Hall, Robert E. 1943- (Hoover Institution Press, 2007)
This new and updated edition of The Flat Tax, called the bible of the flat tax movement by Forbes, explains what's wrong with our present tax system and offers a practical alternative. Hall and Rabushka set forth what many believe is the most fair, efficient, simple, and workable tax reform plan on the table: tax all income, once only, at a uniform rate of 19 percent. - Resumé vydavatel
Originally published: Stanford, Calif. : Hoover Institution Press, 1995. With a new preface.
Keywords: rovná daň -- Spojené státy americké; flat-rate income tax -- United States; elektronické knihy; monografie; electronic books; monographs